Pengaruh Customer Experience, Kepuasan Pelanggan, Dan Brand Image Terhadap Loyalitas Pelanggan Pada Produk Glad2glow (Studi Kasus Pada Mahasiswa Pengguna Produk Glad2glow Di Kota Malang) - Amalia, Rizqi; Asiyah, Siti; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract In the highly competitive beauty industry, companies face increasing challenges in maintaining customer loyalty amid the proliferation of similar skincare products. This study examines the influence of customer satisfaction, brand image, and customer experience on customer loyalty, using Glad2Glow as a case study a skincare brand distributed in Indonesia that competes directly with both local and international brands. Employing a quantitative research method, data were collected from 100 Glad2Glow customers in Malang through purposive sampling and analyzed using SPSS version 22. The findings reveal that all three variables customer experience, brand image, and customer satisfaction have a positive and significant impact on customer loyalty both partially and simultaneously. Multiple linear regression analysis indicates that brand image has the strongest influence, followed by customer satisfaction and customer experience. The results also emphasize that improving emotional and sensory experiences, responding effectively to customer complaints, and building a strong, trustworthy brand image are crucial strategies to retain customers. The study concludes that a holistic approach integrating these factors can help companies like Glad2Glow sustain customer loyalty in a saturated market. Future research is recommended to expand geographic coverage and include other potential variables such as brand trust, price sensitivity, and customer engagement. Keywords: Customer Loyalty, Customer Experience, Brand Image, and Customer Satisfaction